Crimes against the administration of justice. An introduction to the regulation of some figures in the Spanish Penal Code - Polaino-Orts, Miguel (2011)
This study systematizes and critically analyzes the regulation of the crimes contained in articles 1 to 4 of the Spanish Criminal Code in all its forms: judicial corruption, failure to comply with the duty to prevent crimes or promote their prosecution, aiding and abetting (concealment) and arbitrary use of the law. These are offences related to the performance of the judicial function by the judges, the obstruction of said function by a third person not related to the justice system, the wrong understanding of the idea of justice by private persons who attempt to take justice into their own hands or disturb the proper administration of justice. The purpose of prosecuting the referred offences is to protect the legal interest «the Administration of Justice», a concept that is analyzed from an organic, structural and functional viewpoint and its political control.